Klebsiella oxytoca Multiresistant as an Agent of Disseminated Dermatitis in a Dog - Aquino, Simone; Herzig, Karin (Acta Scientiae Veterinariae, 2018)
Background: During the last years, there is a global concern about the increasing levels of antimicrobial resistance in human and veterinary medicine. Klebsiella oxytoca isolates are ubiquitous in nature, including surface water, soils, sewage, and plants. Klebsiella oxytoca is a nosocomial pathogen in humans but few studies reported as a pathogen in dogs and cats. Antimicrobial resistance represents a serious problem due to the increasing prevalence of extended-spectrum β-lactamaseproducing K. oxytoca isolates. The aim of the present study is describe the first clinical case of disseminated dermatitis in a dog caused by K. oxytoca multidrug resistant and the importance of correct protocol treatment. Case: A 4 year-old dog, Shih-tzu, female showed a disseminated dermatitis displayed generalized alopecia, with seborrheic aspect and pruritus, in non-nosocomial conditions in the city of São Paulo. Skin samples were collected and sent to a veterinary microbiology laboratory for bacterial identification and antimicrobial susceptibility testing (AST). The tests demonstrated a Gram negative bacilli, oxidase negative, catalase positive, non motile, DNase negative, glicose fermentative, lactose positive in MacConkey agar. In all biochemical complementary tests the results were indole positive. The strain of K. oxytoca was tested for resistance to the following antibiotics: amikacin, amoxicillin-clavulanic acid, ampicillin, cephalexin, cephalosporin, chloramphenicol, ciprofloxacin, doxycycline, enrofloxacin, gentamicin, imipenem, levofloxacin, marbofloxacin, meropenem, neomycin, sulfamethoxazole/trimethoprim and tetracycline. The AST result demonstrated a resistant Klebsiella oxytoca for 76,4% of tested antibiotics and sensitivity to few antibiotics such as meropenem, imipenem, neomycin, amikacin, sulfamethoxazole and trimethoprim. The initial treatment was performed with meropenem, once the in vitro susceptibility to this antibiotic was demonstrated. However, resistance was observed at 6 days of treatment at a dose of 24 mg/kg /day. After the protocol was changed up to 40 mg/kg/day and maintenance of the dose of 30 mg/kg/day in combination with amikacin (20 mg/kg/day) by continuous administration, the dog had complete remission of symptoms. Discussion: As in human medicine, some microorganisms are becoming multiresistant and emerging pathogens, such as K. oxytoca will be a major challenge for veterinarians, because while at the same time committed to the judicious use of antibiotics, antimicrobial resistance can make infections difficult to treat. The hospitalization of the animal was fundamental for the therapeutic success in the adjustment of doses and the monitoring of the clinical conditions, with remission of the symptoms after 23 days of associated amikacin and meropenem therapy. The cases of K. oxytoca are few discussed or unknown in the routine of veterinary medicine. This scenario should be analyzed in the search for best practices and treatment protocols based on the susceptibility profile of the pathogen. This means prescribing the right antibiotic in the appropriate dose for the target microorganism. Pet owners can help prevent antimicrobial resistance by supporting their veterinarian’s decision to perform tests such as bacterial culture and sensitivity testing as well as hospitalization of the animal for treatment under biosecurity conditions as an important decision-making to avoid cross-contamination between animals and owners, since K. oxytoca is of great importance in animal and human public health.